SISTEM KOMUNIKASI PENYUSUNAN RENCANA AKSI DAERAH PADA PROGRAM SUSTAINABLE DEVELOPMENT GOALs(SDGS)PROVINSI PAPUA - Mogot, Yuni Dahlia; Husnita, Husnita (Jurnal Common, 2021)
Sustainable Development Goals (SDGs) are sustainable development programs which are implemented globally around the world until 2030. Indonesia as a member of the United Nations, is committed to supporting this program through Presidential Regulation No. 59 of 2017 concerning SDGs and their follow-up. Based on data from Bappenas on May 2020, it was recorded that only 25 provinces had finished preparing Regional Action Plan (RAD) as well as the issuance of related regional regulation. Papua Province is one of provinces which cannot complete the development of Regional Action Plan (RAD) in accordance to time which is specified in the SDGs program. The constructivist paradigm was used in this study with qualitative descriptive approach as the method. The research subjects were the Expert Staff of the SDGs Program Implementation Team from Bappenas, the Manager of the Economic Pillars of the SDGs National Secretariat, the staff of the Papua Province Bappeda, and the Managing Editor of merdeka.com. Meanwhile the research objects were government communication system, information flow within government communication system, and communication’s obstacle related to the development of RAD in Papua Province. Data collection techniques were carried out through in-depth interviews, literature reviews, online studies, literature studies, field studies, and documentation. Data validity test were carried out by triangulation technique and membercheck. The result of this study (1) The Papua Province government communication system in the preparation of the Regional Action Plan is to create an organization that forms an information environment among the appointed pillars in the preparation of the Regional Action Plan in Papua Province (2) The flow of the Papua Province government communication system is centralized or top down. Information from Bapennas is always the main person in charge of becoming a benchmark in preparing regional action plans. (3) communication barriers in the Papua Provincial government's communication system related to the preparation of Regional Action Plans are budget issues and understanding of the SDGs themselves. Keywords: Government Communication System, SDGs, Papua Province.